MAKING THE BEST USE OF A TEXTBOOK IN INDONESIAN TERTIARY EFL READING CLASSROOMS - Anna Marietta da Silva (Celt: A Journal of Culture, English Language Teaching & Literature, 2013)
Nowadays, EFL reading textbooks have adjusted their level of linguistic difficulties to their prospective users and provide texts about a variety of topics, detailed explanation of reading skills and practices, not to mention the smart lay-out and good quality of paper, all aiming at facilitating both students and teachers to successfully learn and teach reading, respectively. However, having qualified reading textbooks, teachers cannot take for granted that their students will directly appreciate reading and the textbook selected for the course because in some places extensive reading may not be part of the people's routine, and may not be considered to be very important by the authority. This article provides several useful techniques to take a full advantage of textbooks in A. M. Da Silva, Making the Best Use ofa Textbook 21 EFL reading classrooms in the aforementioned context.